Adverse Price Excursion Risk Prediction for Margin-Call Early Warning in Forex Trading Using Attention-BiLSTM Across Currency Pairs - Gea Natasya; Nandang Taufik WM (Journal of Intelligent Systems Technology and Informatics, 2026)
Leveraged foreign-exchange trading is exposed to rapid adverse price movements that can contribute to margin-call events, yet most prior studies emphasize price or direction forecasting rather than early risk classification. This study uses the Sample, Explore, Modify, Model, and Assess (SEMMA) framework to organize a time-aware experiment on hourly EUR/USD and GBP/USD data from 2010 to 2026. After cleaning, the datasets contained 99,987 and 99,985 observations, respectively. A direction-agnostic maximum adverse excursion proxy labeled whether either a hypothetical long or short position would experience at least 50 pips of adverse movement within five hours. Sixteen technical features were converted into 60-step sequences and evaluated using identical five-fold chronological walk-forward splits. XGBoost, BiLSTM, Attention-BiLSTM, TransformerEncoder, and PatchTST-Lite were compared using training-only scaling and validation-only threshold selection. XGBoost achieved the strongest mean F1-score and ROC-AUC on EUR/USD (0.3710 and 0.7927) and GBP/USD (0.4855 and 0.7847). Attention-BiLSTM remained competitive, with F1-scores of 0.3583 and 0.4825 and the highest mean recall on GBP/USD (0.6680). In a no-retraining EUR/USD-to-GBP/USD transfer test, it obtained an F1-score of 0.5152 and ROC-AUC of 0.7923. Five-fold Wilcoxon tests lacked sufficient resolution to establish superiority. The results support Attention-BiLSTM as a temporally attributable early-warning component, while XGBoost offers the best efficiency-performance trade-off.